KARAKTERISASI DAN SKRINING FITOKIMIA SIMPLISIA BUAH SELUTUI PUKA (Tabernaemontana macracarpa Jack) - Fitri Handayani; Anita Apriliana; Ira Novianti (As-Syifaa Jurnal Farmasi, 2020)
Selutui puka (Tabernaemontana macrocarpa Jack) is a medicinal plant that grows in forests and river banks. This plant can be found in West Kutai, East Kalimantan. Empirically, the use of selutui puka fruit is used as a medicine for toothache and canker sores by boiling it, the cooking water is used by stew. The importance of simplicia characterization is to determine the quality of simplicia which will become the standard for traditional medicine. The purpose of this study was to determine the characteristics of simplicia powder from selutui puka fruit and to determine the class of chemical compounds contained in selutui puka fruit. This research is non experimental. The research starts from sampling, determination, making simplicia, characterization which includes macroscopic test, microscopic test, determination of moisture content, soluble ethanol extract content, water soluble extract content, moisture content, ash content, acid insoluble ash content and phytochemical screening. Data were analyzed using descriptive methods.Macroscopic and organoleptic characterization of simplicia powder has a distinctive aroma (aromatic), bitter fruit flavor, yellowish-brown simplicia powder, white meat, hard and runny meat. Microscopic results of simplicia powder are found in the endocarp, wooden vessels in the form of stairs, trachea, and cork tissue. The level of dissolved ethanol extract was 36%, water juice content was 47%, water content was 8%, ash content was 4.36%, acid insoluble ash content was 0.57%. The results of phytochemical screening contain alkaloids, saponins, and flavonoids.